If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9+x/7=-3
We move all terms to the left:
-9+x/7-(-3)=0
We add all the numbers together, and all the variables
x/7-6=0
We multiply all the terms by the denominator
x-6*7=0
We add all the numbers together, and all the variables
x-42=0
We move all terms containing x to the left, all other terms to the right
x=42
| 0.8x−2=0.48x+6 | | (17+x)2+6x=90 | | (8-3x)5+5x=60 | | n/4=-2.7 | | (x(4-3x)+4(x^2+1))/x^2-4=0 | | 45x-33x+19=25+17 | | 12m+6=15m-3 | | 2x=(90/4) | | 6m+3=29; | | (7-x)5+7x=73 | | 10=-4p-6p | | 6y+1=3y+28 | | 15/18y+1=−6/18y+10/18 | | 5/6y+1=−1/3y+5/9 | | (x)=−3x^2+75 | | −2x^2−9+107=0 | | 160(x-3)=100x | | (3-4x/6)-(2x-3/8)=2-x | | y-4.7=18.6 | | 120=0.30-6x | | -8a-1=2-5a | | 4x+4x^2+3+3x=0 | | 4x+4x^2+3+3x=) | | X+5x-15=x+235 | | 1.4x+3=17 | | 6x+3=9+8x | | 5x+3=6x+15 | | 2x,-3=0 | | 5/6x=8=-11 | | (5x+9x+6x)-(-9x-20x-+6x)=0 | | 5/6x+8=-11 | | 3x2-6x+12=0 |